Risperidone-to-methylphenidate switch reaction in children: three cases - SABUNCUOĞLU, OSMAN TALAT (SAGE PUBLICATIONS LTD, 2007)
As atypical antipsychotics are increasingly used in the treatment of childhood behavioural disorders either as monotherapy or in combination with other medications, there is a need to know more about their safety, in particular during switching to and from methylphenidate treatment, as antipsychotics and methytphenidate have opposing effects on dopaminergic neurotransmission. This report is about three cases of children who developed severe adverse reactions during switching from risperidone to methylphenidate. The first patient was a 6-year-old boy, diagnosed with attention deficit/hyperactivity disorder (ADHC) and oppositional defiant disorder (ODD). He developed severe hyperactivity and agitation on taking methylphenidate after the discontinuation of risperidone treatment. The second patient was a girl of 6, already on risperidone for AND and borderline intellectual functioning when referred. She displayed severe hyperactivity, agitation and irritability upon switching to methylphenidate medication. The third patient was a 15-year-old female adolescent with a similar clinical course as the previous patients. In all the cases described here, it is only with the discontinuation of methylphenidate that the adverse reactions resolved and readministration of methylphenidate in two patients did not produce any adverse effect after a drug-free interval. Functional regulation of certain neuroreceptors during risperidone treatment may lead to altered behaviourat responses upon switching to methylphenidate. Thus, a drugfree interval is recommended in order to prevent adverse reactions.
Keywords: child; conduct disorder; risperidone; methylphenidate; DISRUPTIVE BEHAVIOR DISORDERS; DOPAMINE-RECEPTOR; ADOLESCENTS; ADHD; ANTIPSYCHOTICS; WITHDRAWAL; HUMANS